Find x such that 2 x + 3 4 + 5 x + 4 1 5 = 7 x + 6 3 5 .
Please give your answer to 3 decimal places.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
2 x + 3 4 + 5 x + 4 1 5 = 7 x + 6 3 5
1 0 x 2 + 8 x + 1 5 x + 1 2 2 0 x + 1 6 + 3 0 x + 4 5 = 7 x + 6 3 5
1 0 x 2 + 2 3 x + 1 2 5 0 x + 6 1 = 7 x + 6 3 5
3 5 0 x 2 + 3 0 0 x + 4 2 7 x + 3 6 6 = 3 5 0 x 2 + 8 0 5 x + 4 2 0
7 8 x + 5 4 = 0 ⇒ x = − 0 . 6 9 2
Multiply both sides of the equation by the L C D , but of it is hard to find the L C D , multiply both sides of the equation by the product of the denominators. So, we have
[ 2 x + 3 4 + 5 x + 4 1 5 = 7 x + 6 3 5 ] ( 2 x + 3 ) ( 5 x + 4 ) ( 7 x + 6 )
4 ( 5 x + 4 ) ( 7 x + 6 ) + 1 5 ( 2 x + 3 ) ( 7 x + 6 ) = 3 5 ( 2 x + 3 ) ( 5 x + 4 )
4 ( 3 5 x 2 + 3 0 x + 2 8 x + 2 4 ) + 1 5 ( 1 4 x 2 + 1 2 x + 2 1 x + 1 8 ) = 3 5 ( 1 0 x 2 + 2 3 x + 1 2 )
4 ( 3 5 x 2 + 5 8 x + 2 4 ) + 1 5 ( 1 4 x 2 + 3 3 x + 1 8 ) = 3 5 ( 1 0 x 2 + 2 3 x + 1 2 )
1 4 0 x 2 + 2 3 2 x + 9 6 + 2 1 0 x 2 + 4 9 5 x + 2 7 0 = 3 5 0 x 2 + 8 0 5 x + 4 2 0
3 5 0 x 2 + 7 2 7 x + 3 6 6 = 3 5 0 x 2 + 8 0 5 x + 4 2 0
3 6 6 − 4 2 0 = 8 0 5 x − 7 2 7 x
− 5 4 = 7 8 x
1 3 − 9 = x a n s w e r
I did the same.!
Problem Loading...
Note Loading...
Set Loading...
2 x + 3 4 + 5 x + 4 1 5 2 x + 3 2 8 x + 2 4 + 5 x + 4 1 0 5 x + 9 0 2 x + 3 1 4 ( 2 x + 3 ) − 1 8 + 5 x + 4 2 1 ( 5 x + 8 4 ) + 6 1 4 − 2 x + 3 1 8 + 2 1 + 5 x + 4 6 5 x + 4 6 5 x + 4 1 1 5 x + 1 2 1 3 x ⟹ x = 7 x + 6 3 5 = 3 5 = 3 5 = 3 5 = 2 x + 3 1 8 = 2 x + 3 3 = 2 x + 3 = − 9 = − 1 3 9 ≈ − 0 . 6 9 2 Multiplying both sides by 7 x + 6